Direct observation of ultrafast long-range charge separation at polymer–fullerene heterojunctions - Provencher, Françoise; Bérubé, Nicolas; Parker, Anthony W.; Greetham, Gregory M.; Towrie, Michael; Hellmann, Christoph; Côté, Michel; Stingelin, Natalie; Silva, Carlos; Hayes, Sophia C. (Nature communications, 2014)
In polymeric semiconductors, charge carriers are polarons, which means that the excess charge deforms the molecular structure of the polymer chain that hosts it. This results in distinctive signatures in the vibrational modes of the polymer. Here, we probe polaron photogeneration dynamics at polymer:fullerene heterojunctions by monitoring its time-resolved resonance-Raman spectrum following ultrafast photoexcitation. We conclude that polarons emerge within 300 fs. Surprisingly, further structural evolution on ≲50-ps timescales is modest, indicating that the polymer conformation hosting nascent polarons is not significantly different from that near equilibrium. We interpret this as suggestive that charges are free from their mutual Coulomb potential because we would expect rich vibrational dynamics associated with charge-pair relaxation. We address current debates on the photocarrier generation mechanism at molecular heterojunctions, and our work is, to our knowledge, the first direct probe of molecular conformation dynamics during this fundamentally important process in these materials. Photocarrier generation at organic semiconductor heterojunctions is a crucial process, yet its mechanism and dynamics remain unclear. Here, Provencher et al. show little change in polymer structure following the charge-transfer process and interpret the observation in terms of unbounded electron-hole pairs.